Impact of biomotor dimensions on player quality in young female volleybal players - Milic, M.; Grgantov, Z.; Katic, R. (Collegium Antropologicum, 2013)
A set of 18 test for assessing anthropometric characteristics and 12 tests for assessing motor abilities was used on a sample of 183 young female volleyball players (average age of 13.11 ± 1.07 years). The main goal of this research was to determine the latent structure of biomotor status, as well as relations of that status to situational efficiency in female volleyball players. Situational efficiency of young volleyball players was assessed on a five-point Likert scale, in relation to each individual player`s contribution to the performance of her team, and with regard to the result of that team achieved in the competition. By factor analysis, 3 anthropometric (»endo-mesomorphy«, »longitudinal dimensionality of the skeleton« and »transverse dimensionality of the skeleton«) and 4 motor factors (»explosive power of legs and agility«, »precision«, »explosive power of arms and flexibility« and »balance«) were obtained. Significant impact of morphological-motor factors on situational efficiency of young female volleyball players was obtained by regression analysis. Set of predictor variables accounts for 40% of the total variance of the system. On a univariate level, all extracted factors, except precision and balance, had a significant impact on situational efficiency. Factors named »longitudinal dimensionality of the skeleton« and »explosive power of legs and agility« had the greatest partial contribution in explaining the criteria. Obtained results confirmed previous findings about the importance of individual dimensions of biomotor status for efficiency in volleyball.